Place of Allogeneic Hematopoietic Stem Cell Transplantation in the First Complete Remission in Ph-positive Acute Lymphoblastic Leukemia in Adults - K. S. Afanaseva; A. G. Smirnova; Yu. Yu. Vlasova; I. S. Moiseev; S. N. Bondarenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2023)
Introduction. Ph-positive acute lymphoblastic leukemia (ALL) is a high risk group of B-lineage acute lymphoblastic leukemia (B-ALL). Since tyrosine kinase inhibitors (TKIs) were introduced, controversial data have been obtained on the efficacy of allogeneic hematopoietic stem cell (allo-HSCT) in the first complete remission.The objective was to evaluate the efficacy of allo-HSCT in the first complete remission of Ph-positive ALL in adult patients after remission induction with continuous chemotherapeutic exposure in combination with TKIs.Methods and materials. The retrospective analysis included 74 patients with a median age of 32 years (range 18–59) after allo-HSCT in the first complete remission and 58 patients with a median age of 39 years (range 18–65) in the first complete remission after conservative therapy. Ninety-one per cent and 83 % of patients received imatinib as TKIs in remission induction in the allo-HSCT and conservative therapy groups, respectively. The median time from the first complete remission to allo-HSCT was 7 months (range 2–33). Thirty-six patients (49 %) had positive minimal residual disease (MRD) status prior to allo-HSCT. Eighteen patients (14 %) over 40 years underwent allo-HSCT in the first complete remission.Results. Allo-HSCT improves overall survival (OS) and relapse-free survival (RFS) and by 9 months since the achievement of the first complete remission, they were 70.1 (95 % CI 56.4–88.6) in the allo-HSCT group versus 45.1 (95 % CI 33.4–61.0) in the conservative group, p=0.025 and 63.3 % (95 % CI 47.6–84.1) in the allo-HSCT group versus 44.8 % (95 % CI 33.2–60.4) in the conservative therapy group, p=0.04, respectively. Allo-HSCT in patients over 40 years does not improve 5-year OS and RFS and were 57.2 % (95 % CI 30.0–84.4) versus 59.8 % (95 % CI 36.9– 82.7), p=0.69, and 42.6 % (95 % CI 14.0–71.2) vs. 50.9 % (95 % CI 29.5–72.3), p=0, 88, respectively.Conclusion. Allo-HSCT performed before 9 months from achievement of the first complete remission after induction with imatinib is the preferred method of remission consolidation in patients from 18 to 40 years old. The optimal therapy for patients older than 40 years in the first complete remission is a conservative approach in combination with TKIs.